On the beach at night alone [videorecording (DVD)] - Hong, Sang-su, 1960-; Kim, Min-hŭi, 1982-; Seo, Young-hwa; Jung, Jae-young, 1971- (Cinema Guild, 2018)
Youngshee visits Hamburg and returns to Korea. But as she meets with friends and has her fair share to drink increasingly startling confessions emerge.